Crop insurance, factor allocation, and farmers’ income: evidence from Chinese pear farmers - Cha, Jianping; Deng, Yashan; Zheng, Shaofeng; Li, Feifei (Frontiers in Sustainable Food Systems, 2024)
Crop insurance, as a crucial tool for agricultural risk management, holds significant importance in increasing farmers’ income. This study analyzed the intrinsic relationship and mechanism between crop insurance, factor allocation, and pear farmers’ income. Using field survey data from 1,337 pear farmers in Xixian and Weixian counties in China, we employed OLS regression models and mediation effect models to empirically investigate the direct and indirect impacts of crop insurance on pear farmers’ income. Additionally, we examined the moderating role of agricultural cooperatives and group heterogeneity. The research findings revealed the following: (1) Although crop insurance increases agricultural expenses, it mitigates income losses due to disasters, ultimately leading to a net increase in pear farmers’ income. (2) Crop insurance enhances agricultural labor and machinery inputs, and encourages pear farmers to adopt green production techniques, thereby boosting their income. (3) The beneficial impact of crop insurance on pear farmers’ income is even more pronounced when farmers are members of cooperatives. (4) Heterogeneity analysis showed that for pear farmers who make individual decisions and have smaller land areas, crop insurance can increase their income, while its impact on farmers who make group decisions or have larger land areas is not significant. In conclusion, this study proposes to promote the development of crop insurance, deepen factor market-oriented reforms, support and guide the development of cooperatives, and pay attention to the heterogeneity among different groups of farmers.